Now we get it! : boosting comprehension with collaborative strategic reading - Klingner, Janette; Vaughn, Sharon; Boardman, Alison; Swanson, Elizabeth (San Francisco, CA : Jossey-Bass, 2012)
Includes bibliographical references and index
EDU
Keywords: Mixed ability grouping in education -- United States; Reading -- United States; Reading comprehension; Classroom management -- United States